PERLINDUNGAN TERHADAP PEKERJA/BURUH YANG DIPUTUS HUBUNGAN KERJANYAAKIBAT PELANGGARAN PERJANJIAN KERJA - Hendra Ardyawan, I Putu; Sarjana, I Made; Markeling, I Ketut (Kertha Semaya : Journal Ilmu Hukum; Vol. 02, No. 04, Juni 2014, 2014)
This writing is in accordance with the impact of termination of employment as a result of breach of employment agreement that may lead to disputes. Furthermore, it is necessary to set up expressly for the protection and guarantee the rights and obligations of employers and workers / laborers in the event of termination of employment as a result of breach of employment agreement. Through a normative approach, refers to the study of literature and legislation, in terms of employers cutting jobs on the basis of violations of labor agreements, then the employer must not act arbitrarily and must remain guided by the Employment Agreements and Legislation. Thus, workers / laborers laid off are entitled to protection of their rights in accordance of its work in the form of severance pay, gratuity, cash compensation, and severance payment. Furthermore, to minimize conflict, employers are obliged to make efforts to provide guidance to the prevention of layoffs, laying off workers and provide a transparent explanation to workers / laborers.
Keywords: Workers/laborers, Employers, Working Agreement, and Termination of employment